Clerical Ideology in a Revolutionary Age The Guadalajara Church and the Idea of the Mexican Nation, 1788-1853 - Connaughton, Brian F. (Latin American and Caribbean, 2003)
Clerical Ideology in a Revolutionary Age clearly delineates the role of the Catholic Church in the making of Mexico as a nation. It provides a nuanced sense of clerical thought during the turbulent years leading to and following Mexico's national independence. Connaughton delves deeply into various primary sources from Guadalajara between 1788 and 1853, including printed sermons of high clergymen, contemporaneous newspapers, pamphletry, and pastoral letters. Analyzing this literature in the broader context of the Enlightenment, Connaughton looks at the Enlightenment's potentially corrosive ideas, the rise of liberalism, the complex relationship between Church and State, and the spread of secular mentality. With a balanced approach to clerical discourse, this study of the substance, contradictions, and evolution of Church thinking and political posturing in the face of Bourbon Reforms and the rise of liberalism should be required reading for any student or scholar of Mexican history.